2008
DOI: 10.2967/jnumed.108.055467
|View full text |Cite
|
Sign up to set email alerts
|

Complementary but Distinct Roles for MRI and18F-Fluoromisonidazole PET in the Assessment of Human Glioblastomas

Abstract: Glioblastoma multiforme is a primary brain tumor known for its rapid proliferation, diffuse invasion, and prominent neovasculature and necrosis. This study explores the in vivo link between these characteristics and hypoxia by comparing the relative spatial geometry of developing vasculature inferred from gadolinium-enhanced T1-weighted MRI (T1Gd), edematous tumor extent revealed on T2-weighted MRI (T2), and hypoxia assessed by 18F-fluoromisonidazole PET (18F-FMISO). Given the role of hypoxia in upregulating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(99 citation statements)
references
References 22 publications
5
92
0
2
Order By: Relevance
“…All patient FMISO-PET images were reconstructed with a Hanning filter after scatter correction, resulting in a reconstructed spatial resolution of ∼12 mm (Degrado et al, 1994). Further details of the MRI and PET imaging protocols are given by Rajendran et al (2003), Swanson et al (2009) and in Section 2.4.…”
Section: Case Studymentioning
confidence: 99%
“…All patient FMISO-PET images were reconstructed with a Hanning filter after scatter correction, resulting in a reconstructed spatial resolution of ∼12 mm (Degrado et al, 1994). Further details of the MRI and PET imaging protocols are given by Rajendran et al (2003), Swanson et al (2009) and in Section 2.4.…”
Section: Case Studymentioning
confidence: 99%
“…In general, the hypoxic volume is distinguished with tissue-to-blood ratios ! 1.2 in images acquired 2 h after FMISO injection with venous blood samples [28][29][30][31]. In brain tumor segmentation for MET PET, a tumor-to-normal ratio !…”
Section: Discussionmentioning
confidence: 99%
“…Our results in the first study are consistent with this previous data, except for the grade III patients, as all of our grade III gliomas were FMISO negative. Cher et al used 2 h as the waiting time before conducting the FMISO PET scanning, while the study here used 4 h. Many FMISO PET protocols have used 2 h as the uptake time [24,25,[27][28][29][30][31][32], while Thorwarth et al questioned the adequacy of 2 h for imaging of FMISO [34]. There, the kinetic analysis of dynamic datasets of FMISO PET suggested that the hot spots at 2 h did not reflect actual hypoxia but rather showed a high initial influx of the FMISO due to increased blood flow to the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations